Individual difference correlates of continuing versus ceasing musical participation. (May 2021) - Krause, Amanda E; North, Adrian C; Davidson, Jane W
While researchers have begun to examine how social and emotional investment in music is related to psychological well-being, very little research has considered how best to promote life-long participation in music across the lifespan. One particular gap in the existing literature concerns how and why individuals continue to participate or, instead, cease their participation in musical activities. The current research adopted a social-psychological approach to quantitatively examine the differences between 383 Australian residents who have ceased (44.40%) or currently participate in musical activity (55.60%). Responses to an online questionnaire indicated that current participation in music was associated positively with a preference for reflective and complex music and the World Health Organization–BREF's psychological quality of life dimension, and that current participation in music was associated negatively with peer musical engagement when growing up. Moreover, gender, age, and measures of musical background and experience were not significantly associated with continuing to participate in musical activities. These findings have clear implications for educators' attempts foster continued musical participation.